Social Comparison as Mediator: Does Instagram Intensity Predict Self-Esteem? - Shila Kinari Nayenggita; Made Syanesti Adishesa (Journal of Educational, Health and Community Psychology, 2021)
Instagram is one of the social media platforms that allow people to compare themselves with others (social comparison). Seeing the popularity of SNS, this study explores the role of social comparison as a mediator of the influence of Instagram usage intensity on users' self-esteem. The study was conducted using a mediation test technique through the PROCESS program, with 158 participants (25.95% male and 74.05% female) in the age range 18-25 years (M = 21.53, SD = 1.21). The measurement tools used were the Rosenberg Self-Esteem Scale (RSES), questions relating to social comparison behavior on Instagram, and the average duration spent using Instagram. The findings show that downward social comparison did not act as a mediator in predicting the influence of Instagram usage on young adults' self-esteem. On the contrary, our findings suggested upward social comparison mediates the relationship between Instagram usage and self-esteem. The implication of this study will be further discussed.Â